2013
DOI: 10.3329/icpj.v2i3.13581
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antidiabetic activity in Corallocarpus epigaeus rhizomes

Abstract: From these results it can be understood that plant extract showing its pharmacological action on diabetes between the time intervals of 1-2 hr after its administration. This is exactly what the action that is being observed from the standard Glibenclamide group which also shown its action at its 1-2 hr of administration to the animals. Here the statistically significant action of the higher dose of plant extract can be compared with that of the standard Glibenclamide group. From these results it can be underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The ethyl acetate extract showed the presence of alkaloids, tannins, phenol, flavonoid, steroids, saponin, and glycosides. Gnananath et al (2013) reported that the ethanolic extract of C. epigaeus rhizomes contains phenolic compounds, flavonoids, terpenoids, and phytosterols. Preliminary phytochemical analysis of ethyl acetate extract of C. epigaeus tuber indicated the mix of compounds gives better activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ethyl acetate extract showed the presence of alkaloids, tannins, phenol, flavonoid, steroids, saponin, and glycosides. Gnananath et al (2013) reported that the ethanolic extract of C. epigaeus rhizomes contains phenolic compounds, flavonoids, terpenoids, and phytosterols. Preliminary phytochemical analysis of ethyl acetate extract of C. epigaeus tuber indicated the mix of compounds gives better activity.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaloids are also used as starting materials in the manufacture of steroidal drugs and carry out protective functions in animals, thus are medicinal especially steroidal alkaloids (Maxwell et al, 1995). Isolated pure plant alkaloids and their synthetic derivatives are used as basic medicinal agent for their anthelmintic effects (Gnananath et al, 2013). The presence of these secondary metabolites has contributed to its medicinal value as well as physiological activity (Lewis and Elvin-Lewis., 1977).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. epigaeus is commonly called as Akas Gaddah. C. epigaeus plant is one such important medicinal plants used in treating syphilitis, venereal complaints and chronic dysentery (Kothawade and Siddiqui 2018); it is also effectively used to cure diabetes (Gnananath et al 2013), snakebites (Chandrakala et al 2013) and rheumatism (Uthrapathy et al 2011).…”
Section: Introductionmentioning
confidence: 99%